Comparative assessment of using Miscanthus × giganteus for remediation of soils contaminated by heavy metals: a case of military and mining sites - Nurzhanova, Asil; Pidlisnyuk, Valentina; Abit, Kamila; Nurzhanov, Chingiz; Kenessov, Bulat; Stefanovska, Tatyana; Erickson, Larry (Environmental science and pollution research international, 2019)
Contamination of soil by heavy metals is among the important environmental problems due to their toxicity and negative impact to human health and the environment. An effective method for cleaning the soil from heavy metals is phytoremediation using the second-generation bioenergy species Miscanthus × giganteus. The purpose of this research is to study the benefits of M. × giganteus cultivation at the soils taken from the mining and former military sites contaminated by As, Pb, Zn, Co, Ni, Cr, Cu, V, Mn, Sr, and U as well as at the soil artificially contaminated by Zn and Pb, to evaluate the physiological parameters of the plant, to establish peculiarities of the phytoremediation process, and to characterize the behavior of the plant in relation to the nature and concentrations of the metals in the soils. Results showed that M. × giganteus was resistant to heavy metals (tolerance index ≥ 1) and that the greatest portion of metals accumulated in the root system. The morphological parameters of the plant while grown on different soils are influenced by soil type and the content of contaminants. The stress effect while growing M. × giganteus on soil artificially contaminated by Zn and Pb was evaluated by measuring the content of pigments (chlorophylls a, b, and carotenoids) in the plant's leaves. The decrease in the total content of chlorophylls, Сa + b/Сcar and transpiration rate of water along with the increase in the water absorbing capacity were observed. The accumulation of heavy metals in different parts of the plant was determined; bioaccumulation coefficient and values of translocation factor were calculated. The obtained results showed that M. × giganteus was an excluder plant for nine highly toxic elements (As, Pb, Zn, Co, Ni, Cr, Cu, V, U) and an accumulator species for the moderately dangerous elements (Mn, Sr). Further research will be focused on the extraction of stable stimulated plant-growth-promoting rhizobacteria from the rhizosphere of M. × giganteus and formulation on that base the plant-bacterial associations as well as on the comparison of the plant physiological parameters, biochemical soil activity, and accumulation of heavy metals in the Miscanthus tissues between first and second vegetations.
Keywords: rostliny; Metals, Heavy; látky znečišťující půdu; rhizosféra; Biodegradation, Environmental; biodegradace; Bioaccumulation; ozbrojené síly; Military Personnel; Translocation factor; Poaceae; Plants; těžké kovy; půda; Mining; Soil Pollutants; Soil phytoremediation; Bioenergy plant; lipnicovité; Heavy metals; hornictví; Rhizosphere; Miscanthus × giganteus; Soil